2018
DOI: 10.1016/j.ultras.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of guided-wave ultrasound propagation in composite laminates: Benchmark comparisons of numerical codes and experiment

Abstract: Ultrasonic wave methods constitute the leading physical mechanism for nondestructive evaluation (NDE) and structural health monitoring (SHM) of solid composite materials, such as carbon fiber reinforced polymer (CFRP) laminates. Computational models of ultrasonic wave excitation, propagation, and scattering in CFRP composites can be extremely valuable in designing practicable NDE and SHM hardware, software, and methodologies that accomplish the desired accuracy, reliability, efficiency, and coverage. The devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“…From the contemporary research on delamination in laminated composites, it can be found that most of the research efforts are dedicated to the use of higher-frequency guided waves (e.g., Lamb waves), acoustic emission/acoustic ultrasonic, and mode shape curvatures for the detection, quantification, and localization of delamination [43][44][45][46][47][48][49]. This paper proposes a deep learning framework for the assessment of delamination in piezo-bonded laminated composites using low-frequency structural vibration responses.…”
Section: Introductionmentioning
confidence: 99%
“…From the contemporary research on delamination in laminated composites, it can be found that most of the research efforts are dedicated to the use of higher-frequency guided waves (e.g., Lamb waves), acoustic emission/acoustic ultrasonic, and mode shape curvatures for the detection, quantification, and localization of delamination [43][44][45][46][47][48][49]. This paper proposes a deep learning framework for the assessment of delamination in piezo-bonded laminated composites using low-frequency structural vibration responses.…”
Section: Introductionmentioning
confidence: 99%
“…Limited publications were found for the analysis using 3D FEM models due to the large computational demand. However, several FE simulation tools have been used in a previous study and found that all of the tools are adequate to simulate the guided waves in composite laminate through 3D FEM [9]. Studies in [10], [11] show that 3D simulations can accurately predict the scattering characteristics of guided waves by using simple rectangular-shaped defects, where both FE and experimental results show comparable results.…”
Section: Introductionmentioning
confidence: 99%
“…The most cost-effective and convenient approach is typically FEM modelling due to several commercially available products such as ANSYS, ABAQUS and Patran [2]. As such, many authors have simulated Lamb waves using FEM in a wide range of studies (see Figure 6) [1,8,10,11,14,19,20,[26][27][28][29]. Su outlined the two main requirements for modelling Lamb waves via FEM; activation of the wave pulse and acquisition of the response [2].…”
Section: Modelling Lamb Waves Using the Finite Element Methods (Fem)mentioning
confidence: 99%
“…Leckey et al compared several numerical codes (ABAQUS, ANSYS and COMSOL) in simulating guided ultrasonic waves in composite laminates [26]. In this study a 3-cycle Hanning windowed sine wave was used to actuate the A0 Lamb mode [26].…”
Section: Modelling Lamb Waves Using the Finite Element Methods (Fem)mentioning
confidence: 99%
See 1 more Smart Citation